Measuring real-time performance - Ng, Gerald Yuen Cheon. (2009)
The aim of this project is to implement the benchmark, Rhealstone metric as proposed by Kar and Porter , to measure the real-time capabilities of the AT&T System V UNIX operating system. Rhealstone metric chiefly helps developers select "real-time computer systems" appropriate for their applications. It won't measure how good the complete solution is, instead it is an engineering measurement targeted specifically toward true multitasking solutions. For our study, we use Rhealstone metric to compare the real-time capabilities of different flavours of SYSTEM V UNIX running on various hardware platforms.